METHODOLOGY FOR ORGANIZING INDEPENDENT LEARNING IN MASTERING THE ELECTROMAGNETISM UNIT BASED ON AN INDIVIDUAL LEARNING TRAJECTORY FOR PROSPECTIVE PHYSICS TEACHERS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article presents a methodology for organizing independent learning in the teaching of the electromagnetism unit of physics based on an individual learning trajectory (ILT). The theoretical foundations of the approach and methods for its practical implementation are described. Designed for pre-service physics teachers, this approach uses individualized assignments and a portfolio-based assessment to create a learning process tailored to each student. The significance of the proposed methodology lies in its ability to help students gain a deep understanding of electromagnetism while developing their professional competencies and self-directed learning skills.